Studi Populasi Siamang (Symphalangus Syndactylus Raffles, 1821) di Hutan Adat Guguk Kabupaten Merangin Provinsi Jambi - Ratna Sari Gultom; Apriza Hongko Putra; Rozana Zuhri (BIOCOLONY, 2019)
This research was motivated by the lack of research on the siamang in hutan Adat Guguk of Merangin Regency, Jambi Province. The purpose of study was to determine and describe the siamang population based on the size of the group, the composition of age and sexual rasio in the forest of Adat Guguk Merangin Regency, Jambi Province. The method used is a concentreated area method with three observation stations and used the Rappid Assesment to record food and rest vegetation of siamang. Data was analyzed descriptively. The result showed that the siamang group found in the study area were 2 groups (5 individuals ) and 1 solitary male. The distribution of age classes in the individual adult phase is 5 individuals the sapling phase was 1 individual and the baby phase werw not found in the siamang group in the hutan Adat Guguk. The seksual ratio value of the siamang group in the adult phase is 1:1, for the solitary male the sexual ratio is 1:0 and ato the juvenile phase could not identyfied the sex of simang because the sexual chaarteristic of had not developed perfectly.